Preoperative Fasting Duration and Associated Factors in Pediatric Patients Undergoing Elective Surgery: A Prospective Study - Khatri, Sandeep; Bhattarai, Amit Sharma; Shakya, Bigen Man; Shrestha, Pramesh Sunder (Journal of Institute of Medicine Nepal, 2025)
Introduction Preoperative fasting prevents gastric aspiration, yet pediatric patients often endure prolonged fasting despite “6-4-2” guidelines. This study aims to determine average fasting durations for solid and liquid food in Nepal and identify causes of prolonged fasting and non-adherence to fasting guideline.MethodsA total of 139 children up to 12 years were enrolled in this prospective observational study. Data about the fasting duration and the various causes of prolonged fasting were collected in the pre-operative holding area using a preformed questionnaire. Using the SPSS version 26, the median duration of fasting for each category was calculated, along with their interquartile range (IQR), the percentage of non-adherence, and the causes of prolonged fasting, as well as the signs and symptoms observed in children.ResultsAmong 139 patients, 133(95.7%) of patients were not compliant with the fasting guideline. The median (IQR) duration of fasting for solid food, breast milk, and clear liquid was 12(3) hours, 5(2.75) hours, and 6(8) hours respectively. The major causes of prolonged fasting were poor NPO adherence, receiving different instructions from different individuals, and not receiving instructions according to the OT list. Among 139 patients, 57(41%) were thirsty, 31(22%) were irritable or crying, 41(29%) had dry mouth/lips with 4(2.8%) patients having skin pinch test positive and 4(2.8%) patients were dehydrated meeting the diagnostic criteria for dehydration.ConclusionThis study demonstrates that fasting durations significantly exceed international guidelines in Nepal, primarily due to inconsistent instructions and non-individualized scheduling.